2020
DOI: 10.1021/acsphotonics.0c01311
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Field-Induced Metastable States in the Wetting Layer: Detected by the Fluorescence Decay Time of InAs/GaAs Single Quantum Dots

Abstract: We report a new way to slow down the spontaneous emission rate of excitons in the wetting layer (WL) through radiative field coupling between the exciton emissions and the dipole field of metal islands. As a result, a long-lifetime decay process is detected in the emission of InAs/GaAs single quantum dots (QDs). It is found that when the separation distance from WL layer (QD layer) to the metal islands is around 20 nm and the islands have an average size of approximately 50 nm, QD lifetime may change from appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(103 reference statements)
1
9
1
1
Order By: Relevance
“…To achieve γ/γ 0 → 0, here we chose Ag nanoparticles for generating the localized surface plasmon field owing to the fact that the scattering field is highly correlated with the extinction cross section of the metal nanoparticles. Compared with our previous article in which the metal steel islands were used to control the exciton emission decay time, 17 here it is found that Ag nanoparticles can generate a much stronger localized plasmon field and more effectively inhibit exciton spontaneous radiation. We have calculated the extinction cross section…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…To achieve γ/γ 0 → 0, here we chose Ag nanoparticles for generating the localized surface plasmon field owing to the fact that the scattering field is highly correlated with the extinction cross section of the metal nanoparticles. Compared with our previous article in which the metal steel islands were used to control the exciton emission decay time, 17 here it is found that Ag nanoparticles can generate a much stronger localized plasmon field and more effectively inhibit exciton spontaneous radiation. We have calculated the extinction cross section…”
contrasting
confidence: 64%
“…Since the excitons in the WL have exciton dipoles oriented parallel to the plane of the sample surface, under the conditions of the metal nanoparticle radius R ≪ λ and weak coupling, the total scattering field of the metal nanoparticles will affect the electromagnetic LDOS around the excitons in the WL. The normalized decay rate of the exciton dipoles in the WL can be written as where is the wave vector in the medium, λ the wavelength in vacuum, n the refractive index of the medium, N is the average particle number of metal nanoparticles, and z = D + R is the distance between the emitter and the center of the metal nanoparticle. Here D is the thickness of the GaAs space layer ( D = 10, 15, 19, 25, 35 nm for different samples) and R is the radius of the Ag nanoparticle.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 引 言 半导体量子点(QD)由于结构上存在三维限制和类原子特性,因而具有 一系列独特的性质,如量子点可作为理想的固态单光子源,单光子源在量子密 钥等量子信息方面有着重要的应用 [1,2] .相关地,如何调控单量子态的光学跃迁 一直是该领域的重要研究方向.基于 Fermi 黄金定律,量子点激子的自发辐射速 率正比于激子所处位置的电磁场的态密度 [3,4] .由 Purcell 理论知 [5] ,改变激子所 在位置的电磁场局域态密度(LDOS) ,可以改变量子点中激子的自发辐射速率, 进而可以调控半导体量子点自发辐射.LDOS 的改变可以基于激子的辐射场与散 射场之间的相互干涉 [3,6] [3,7] ,最近在二维半导体材料 中也有类似的发现 [8,9] .除了平面反射镜外,实验和理论工作显示,通过在发光 偶极子附近放置金属腔可以调控偶极子自发辐射 [4,[10][11][12][13][14][15] ,而其中球形的金属纳米 颗粒可以产生局域电场的增强效应 [14,[16][17][18] ,也受到了广泛的关注.不过,这些 研究主要集中在如何利用金属局域场来提高量子点激子的发光效率 [19,20] ,而对 于抑制激子自发辐射的研究较少 [21,22] .抑制激子的自发辐射,即制备长寿命的 激子态恰是激子的玻色-爱因斯坦凝聚研究中的必要条件 [23,24] .本文在实验上使 用金(Au)纳米颗粒抑制 InAs/GaAs 量子点浸润层(WL)激子的自发辐射速率, 𝑖𝑘𝑟 (2)…”
unclassified